Epidemiology of anorexia nervosa in Japanese adolescents - Hotta, Mari (Biopsychosoc Med, 2015)
BACKGROUND: No epidemiologic survey examining eating disorders in Japan has been done at a national level since 1992. The prevalence of anorexia nervosa, as assessed by questionnaires to hospitals, is thought to be underestimated because patients with anorexia nervosa tend to avoid consultations. In conformity with the School Health and Safety Act of Japan, schools are required to have physicians perform a medical examination of students every year. The teachers in charge of health education and school physicians determine the height, weight, and health condition, and examine the medical records of each student. Therefore, we as members of the Survey Committee for Eating Disorders of the Japanese Ministry of Health, Labour, and Welfare conducted an epidemiologic survey using questionnaires sent to schools in seven prefectures to determine the current prevalence of anorexia nervosa among adolescents. METHODS: We sent a questionnaire to elementary, junior high, and senior high schools. Questionnaires contained items on the number of students, patients with anorexia nervosa in each grade who were diagnosed by specialists, and students who the school physician strongly suspected to have anorexia nervosa but who did not undergo a clinical examination in a medical institution. RESULTS: We found patients of both sexes with anorexia nervosa aged 9–10 years in elementary schools. The point prevalence of anorexia nervosa for girls, including strongly suspected cases, in the three grades of junior high school and three grades of senior high school were 0–0.17 %, 0–0.21 %, 0.17-0.40 %, 0.05-0.56 %, 0.17-0.42 % and 0.09-0.43 %, respectively. We also confirmed a prominent sex difference in the prevalence of anorexia nervosa. The prevalence of boys was one third that of girls in some prefectures. One third to one half of diagnosed and strongly suspected students with anorexia nervosa had not received medical consultation or treatment. CONCLUSIONS: Although the prevalence of anorexia nervosa had regional differences in Japan, it has reached levels comparable to those in Western societies. Because no eating disorder center exists and the treatment environment is poor, national action to address this disease is a pressing need in Japan.